2018
DOI: 10.1016/j.clinthera.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flibanserin on the Pharmacokinetics of a Combined Ethinylestradiol/Levonorgestrel Oral Contraceptive in Healthy Premenopausal Women: A Randomized Crossover Study

Abstract: Pretreatment with flibanserin 100 mg once daily for 2 weeks did not produce a clinically relevant change in oral contraceptive drug exposure following single-dose administration of ethinylestradiol/levonorgestrel. This finding is relevant to women with hypoactive sexual desire disorder who might prefer oral contraceptives to other forms of birth control. EudraCT No: 2006-006960-46.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Sexual dysfunction as a side effect is often attributed to monoaminergic and dopaminergic activity of antidepressants (Clayton et al, 2014). The pharmacological profile of pimavanserin may explain improvements in sexual dysfunction observed with in this study and is consistent with the hypothesis that 5‐HT 2 antagonism may improve sexual functioning (Johnson‐Agbakwu et al, 2018; Stryjer et al, 2009). The effects of pimavanserin on sexual dysfunction in this study also could be attributed to improvements in depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sexual dysfunction as a side effect is often attributed to monoaminergic and dopaminergic activity of antidepressants (Clayton et al, 2014). The pharmacological profile of pimavanserin may explain improvements in sexual dysfunction observed with in this study and is consistent with the hypothesis that 5‐HT 2 antagonism may improve sexual functioning (Johnson‐Agbakwu et al, 2018; Stryjer et al, 2009). The effects of pimavanserin on sexual dysfunction in this study also could be attributed to improvements in depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…CLARITY was a randomized, double‐blind, and placebo‐controlled study that demonstrated robust efficacy of adjunctive pimavanserin in patients with MDD and an inadequate response to treatment with an SSRI or SNRI (Fava et al, 2019). Given the fact that pimavanserin acts as a potent inverse agonist at 5‐HT 2A receptors, and to a lesser extent at 5‐HT 2C receptors (Vanover et al, 2006), and that 5‐HT 2 antagonism has been shown to be helpful in the treatment of sexual dysfunction (Johnson‐Agbakwu, Brown, Yuan, Kissling, & Greenblatt, 2018; Stryjer et al, 2009), we conducted additional analyses from CLARITY to address (a) whether adjunctive pimavanserin augments or improves sexual functioning versus placebo; (b) if this effect is accounted for by changes in depression severity; and (c) if there are baseline factors that moderate the improvement in sexual function with pimavanserin.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior causes a reduction in the serotonin level in the brain, as well as the elevation of norepinephrine neurotransmitters, which results in the improvement of sexual functioning in premenopausal women [4][5][6]. Thus, it was approved by the FDA in 2015 for the management of patients with hyposexual desire disorder (HSDD) [7]. The FDA approved a dose of 100-mg FB/day, which is rapidly absorbed after oral administration and excreted as unchanged drug in the urine [8].…”
Section: Introductionmentioning
confidence: 99%
“…These neurotransmitters have been associated with excitatory and inhibitory responses to sexual cues implicated in HSDD [ 13 ]. Clinical trials have demonstrated that subjects experienced improved satisfying sexual events after taking flibanserin compared to that of the control group [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Flibanserin was initially rejected for approval by the FDA in 2010 due to concerns over efficacy and safety data [ 53 , 65 ].…”
Section: Current Treatmentmentioning
confidence: 99%